Mapping Priority Improvements in Quality Improvement Projects: An Integrated Study of Quality and Risk Management - Sulistiyowati, Wiwik; Suef, Mokhammad; Singgih, Moses Laksono (Journal of Posthumanism, 2025)
This study develops a model to identify critical success factors that determine the success of quality improvement projects by analyzing the relationships between quality management principles, project implementation, and risk management and determining priority factors that require improvement. This study uses an approach that combines three main methods. The first method analyzes the relationship between various factors that affect project success. The second method identifies low-performing aspects that require prioritization for improvement. The third method aims to identify the root cause of problems in quality improvement projects. The study results indicate that quality management principles, risk management, and project implementation have a direct impact on the success of quality improvement projects. However, the role of project implementation as a mediator between risk management and project success is not very strong, although it significantly affects quality management principles. Key factors needing improvement include employee involvement, leadership, and quality planning. This study offers insight into how quality and risk management can support one another, helping to identify key factors for improvement and providing a more comprehensive approach to enhancing quality.